The effectiveness of self-regulated learning (SRL) interventions on L2 learning achievement, strategy employment and self-efficacy: A meta-analytic study - Chen, Jing (Frontiers in Psychology, 2022)
Interventions that incorporated the teaching of self-regulated learning (SRL) strategies are assumed to be effective in improving students’ second language (L2) performance as they support students’ SRL activity and self-efficacy. Nevertheless, previous meta-analyses largely focused on students’ language learning achievement, while neglecting the instructional effects on their SRL strategy use and self-efficacy, two key factors in SRL models. This meta-analytic study was thus conducted to address the gap by synthesising the evidence of SRL interventions in influencing students’ L2 learning achievement, strategy use, and self-efficacy. The largest effect was obtained for L2 learning achievement (g = 1.39), followed by self-efficacy (g = .45) and strategy use (g = .40). Moderator analysis revealed similar instructional effects on students of different age groups and education levels. The duration and intensity of intervention significantly moderated the effectiveness of SRL interventions in the L2 context, especially for strategy use and self-efficacy. The findings obtained in the current study could inform practitioners and researchers of the cumulative effects of SRL interventions in L2 classrooms and study design and student characteristics that moderate the instructional effectiveness.